1998
DOI: 10.1017/s1355617798001064
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI correlates of recognition memory in Alzheimer's disease

Abstract: Neuroimaging and lesion studies have demonstrated that hippocampal volume correlates with memory performance, but material-specific lateralization of this structure-function relationship has been inconsistent. This MRI study examined the relative contributions of left and right temporal lobe volumes to verbal and nonverbal recognition memory in a group of 20 Alzheimer's disease (AD) patients. There was a significant relationship between extent of right hippocampal and right temporal gray matter tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 36 publications
4
37
0
1
Order By: Relevance
“…The current results are consistent with existing literature demonstrating correlations between hippocampal volume loss and a number of visual and verbal performance measures (Cahn et al, 1998;Deweer et al, 1995;Fama et al, 1997;Petersen et al, 2000), including the memory subtests of dementia status tests (Deweer et al, 1995;Fama et al, 1997;Stout et al 1996). Stronger associations have been…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current results are consistent with existing literature demonstrating correlations between hippocampal volume loss and a number of visual and verbal performance measures (Cahn et al, 1998;Deweer et al, 1995;Fama et al, 1997;Petersen et al, 2000), including the memory subtests of dementia status tests (Deweer et al, 1995;Fama et al, 1997;Stout et al 1996). Stronger associations have been…”
Section: Discussionsupporting
confidence: 91%
“…Impaired memory function is a critical feature in the diagnostic criteria for probable Alzheimer's disease (McKhann et al, 1984). Hippocampal atrophy in AD, demonstrated with structural MRI, is associated with impaired performance on both verbal and visual memory tasks (Cahn et al, 1998;Deweer et al, 1995;Fama et al, 1997;Petersen et al, 2000), including the memory subtests of dementia status tests (Deweer et al, 1995;Fama et al, 1997;Stout et al 1996). Data from Jernigan's laboratory (Stout et al, 1999) showed significant correlations between the volume of mesial temporal lobe and the immediate recall measures, as well as recognition discriminability, on the California Verbal Learning Test (CVLT; Delis et al, 1987) in demented patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When cortical gray matter, hippocampal volumes and white matter signal hyperintensities were simultaneously entered into a regression model predicting immediate recall, only cortical gray matter volume explained a significant proportion of the variance. This finding highlights the importance of including non-hippocampal structures in correlational studies of memory (Cahn et al, 1998;Kopelman et al, 2001) and is consistent with other studies that have shown specificity in the relationship between memory and medial temporal structures (Cahn et al, 1998;Fama et al, 1997).…”
Section: Discussionsupporting
confidence: 90%